2018
DOI: 10.1089/aid.2017.0310
|View full text |Cite
|
Sign up to set email alerts
|

Shifting the HIV Paradigm from Care to Cure: Proceedings from the Caribbean Expert Summit in Barbados, August 2017

Abstract: The CCAS EXPERT SUMMIT convened an array of international experts in Barbados on August 27–31, 2017 under the theme “From Care to Cure–Shifting the HIV Paradigm.” The Caribbean Cytometry & Analytical Society (CCAS) partnered with the Joint United Nations Programme on HIV/AIDS (UNAIDS) to deliver a program that reviewed the advances in antiretroviral therapy and the public health benefits accruing from treatment as prevention. Particular emphasis was placed on reexamining stigma and discrimination through a cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 58 publications
(54 reference statements)
1
2
0
Order By: Relevance
“…Furthermore, with 39% of HCP stating the Hospital/VCT Center is ill-equipped to handle HIV patients, it stands to reason why some HCP remain fearful of working with PLWH, as shown by our study. These findings are consistent with other studies in revealing that the majority of HCP most often describe their place of work as unequipped to manage HIV patients [31,32]. In light of these findings, the government and community must commit to upgrading their healthcare facilities to ensure an ideal work environment for staff that makes possible the delivery of quality health care for all patients, regardless of their health status.…”
Section: Juniper Online Journal Of Public Healthsupporting
confidence: 88%
“…Furthermore, with 39% of HCP stating the Hospital/VCT Center is ill-equipped to handle HIV patients, it stands to reason why some HCP remain fearful of working with PLWH, as shown by our study. These findings are consistent with other studies in revealing that the majority of HCP most often describe their place of work as unequipped to manage HIV patients [31,32]. In light of these findings, the government and community must commit to upgrading their healthcare facilities to ensure an ideal work environment for staff that makes possible the delivery of quality health care for all patients, regardless of their health status.…”
Section: Juniper Online Journal Of Public Healthsupporting
confidence: 88%
“…The studies rarely provided a priori power analysis to estimate a sufficient size of study sample to be able to detect changes in psychological outcomes. Despite medical advances in the prevention and care of HIV [37, 38], there are emotional and social problems, such as stigma, that may make the burden of disease challenging not only for the infected individual but also for the family [38–40]. Since study findings indicated changes in psychosocial outcomes for individuals with preexisting stress or anxiety [14, 23, 25] but are not statistically significant in other populations, future intergenerational interventions should be expanded in scope to focus more on PLH with preexisting psychological stress.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the elimination of persistent HIV within infected patients will require effective treatments that eradicate cells harboring latent provirus genomes. To date, noteworthy HIV eradication programs such as UN/AIDS 90-90-90, which utilize global epidemiological strategies and mathematical models, have been implemented by the World Health Organization (WHO) with the goal of controlling HIV disease among the global population, focusing on developing nations [3, 4]. Within infected individuals, despite the remarkable successes in reducing morbidity and mortality of people living with HIV, eradication of the virus is limited by persistent latently HIV-infected cellular reservoirs.…”
Section: Introductionmentioning
confidence: 99%